Noise Measurements in Timber Industries - Vasiliki Dimou (University of Zagreb, Faculty of Forestry and Wood Technology, 2014)
The intensification of industrial production and the concurrent increase in machine operation speeds has led to the rise in the intensity of noise generated in most workplaces. The purpose of the present paper is to investigate occupational noise exposure in timber processing units. For this reason, a number of measurements were carried out in various parts of three sawmills. Maximum allowable exposure limits (permissible levels) were set at 85 dB(A) for the production area and warehouses, and 55 dB(A) for offi ces. According to the results of the study, the production area in a sawmill gives rise to higher levels of noise compared to warehouses and offices, which significantly exceed maximum permissible levels. More specifically, the highest noise levels recorded were found to be produced by cutting machinery. In such cases it is imperative that employees be protected either with the use of personal hearing protectors or with the implementation of a regular break scheme. In addition, substantial reduction in noise levels can be achieved with the use of other protective measures such as control of noise at its source or in its path.